2000
DOI: 10.1016/s1097-2765(00)00076-9
|View full text |Cite
|
Sign up to set email alerts
|

A Histone Variant, Htz1p, and a Sir1p-like Protein, Esc2p, Mediate Silencing at HMR

Abstract: Silencing at HMR requires silencers, and one of the roles of the silencer is to recruit Sir proteins. This work focuses on the function of Sir1p once it is recruited to the silencer. We have generated mutants of Sir1p that are recruited to the silencer but are unable to silence, and we have utilized these mutants to identify four proteins, Sir3p, Sir4p, Esc2p, and Htz1p, that when overexpressed, restored silencing. The isolation of Sir3p and Sir4p validated this screen. Molecular analysis suggested that Esc2p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
115
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 50 publications
4
115
0
1
Order By: Relevance
“…We confirmed this nuclear localization of Gpd1p by double fluorescence microscopy co-localization of the GFP signal with Htz1p-RFP, a well characterized nuclear histone variant (Fig. 5B) (51). This shift of Gpd1p to the nucleus was common to exposure to a number of different stress conditions, including treatment with NaCl (0.3 and 0.6 M), 1 M sorbitol, 2.5 mM dithiothreitol, or 37°C heat shock (data not shown).…”
Section: Dynamic Changes In Subcellular Distribution Of Gpd1p Betweensupporting
confidence: 63%
“…We confirmed this nuclear localization of Gpd1p by double fluorescence microscopy co-localization of the GFP signal with Htz1p-RFP, a well characterized nuclear histone variant (Fig. 5B) (51). This shift of Gpd1p to the nucleus was common to exposure to a number of different stress conditions, including treatment with NaCl (0.3 and 0.6 M), 1 M sorbitol, 2.5 mM dithiothreitol, or 37°C heat shock (data not shown).…”
Section: Dynamic Changes In Subcellular Distribution Of Gpd1p Betweensupporting
confidence: 63%
“…For example, H2A.Z seems to be implicated in both the activation and repression of transcription (13,20,22,31). The reported data suggested that H2A.Z is involved in chromosome segregation (29).…”
mentioning
confidence: 88%
“…In this screen, wild-type ESC2 silences the ADE2 reporter at HMR, giving rise to red colonies, and null or partial esc2 function yields white, pink, and/or sectored colonies (Dhillon and Kamakaka 2000;Cuperus and Shore 2002). esc2 mutants were integrated into the genome at the ESC2 locus under control of the native promoter and screened for function.…”
Section: Resultsmentioning
confidence: 99%
“…Silencing assay: HMRTADE2 silencing was performed as described previously (Chi and Shore 1996;Dhillon and Kamakaka 2000). Isogenic strains were grown in YPD culture to early logarithmic phase (2-5 3 10 6 cells/ml) at 30°, and serial dilutions were plated on YPD plates to obtain welldispersed, discrete colonies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation